2020
DOI: 10.3389/fpsyg.2020.01574
|View full text |Cite
|
Sign up to set email alerts
|

Marriage and Post-stroke Aphasia: The Long-Time Effects of Group Therapy of Fluent and Non-fluent Aphasic Patients and Their Spouses

Abstract: Background Studies of therapy influence on after-aphasia marital relations are lacking. Much needs to be learned about the range of factors associated with couples benefiting from therapy. Understanding these issues is key to facilitating optimal post-aphasia outcomes from the perspective of the patient and his caretaking spouse. This paper reports an evaluation of a group therapy intervention conducted with aphasic people and their life partners. Methods The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…40 Aside from the largest study with 349 caregivers, 24 there were 5 studies with over 100 caregivers or dyads 19,26,28,33,34 ; however, 2 of the studies reported findings using the same sample. 33,34…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…40 Aside from the largest study with 349 caregivers, 24 there were 5 studies with over 100 caregivers or dyads 19,26,28,33,34 ; however, 2 of the studies reported findings using the same sample. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies reviewed, only 3 caregiver 19,20,28 and 3 dyad 32–34 intervention studies reported testing for significance in survivor outcomes. One caregiver intervention study reported improvements in survivor cognition, depression, and anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations